STUDY OF SUBCELLULAR DISTRIBUTION OF CRYSTALLINE MESO-TETRA(3-PYRIDYL)BACTERIOCHLORIN NANOPARTICLES - Yu. S. Maklygina; A. V. Borodkin; A. V. Ryabova; D. V. Pominova; E. A. Makarova; E. A. Lukyanets; V. B. Loshchenov (Biomedical Photonics)
The results of the study of subcellular distribution of molecular meso-tetra(3-pyridyl)bacteriochlorin nanocrystals proposed as therapeutic agents for photodynamic therapy are represented in the article. Investigations and measurement of spectroscopic properties of molecular crystals of near-infrared photosensitizer were conducted using special device complex based on fiber-optic spectrometer. Investigation and analysis of the pattern of subcellular accumulation of meso-tetra(3-pyridyl)bacteriochlorin in molecular (dimethyl sulfoxide (DMSO) as solvent) and nanocrystalline forms on different cell lines: human monocytes (THP-1), human cervical cancer cells (HeLa) and mouse malignant brain tumor cells (glioma C6). The dynamics of subcellylar accumulation of the agent at concentration of 5 and 10 mg/l was assessed with laser microscope-spectrum analyzer and by confocal microscopy. The study showed that in the course of interaction with cell lines molecular nanocrystals of the agent developed ability to fluorescence. Hence, in the cellular environment meso-tetra(3-pyridyl) bacteriochlorin nanoparticles became phototoxic giving opportunities for their use for fluorescence diagnosis and photodynamic therapy. Specific role of meso-tetra(3-pyridyl)bacteriochlorin in the range of photosensitizers is determined by its spectral characteristics, i.e. absorption and fluorescence in near-infrared band, which allows measuring and affecting on deeper layers of biotissue. Thus, the use of meso-tetra(3-pyridyl)bacteriochlorin nanoparticles as nanophotosensitizers may improve the efficacy of diagnosis and treatment of deep-seated tumors.